Donald Trump’s foreign policy and its impact on Latin America - Novak, Fabián; Namihas, Sandra (Pontificia Universidad Católica del Perú. Instituto de Estudios Internacionales (IDEI), 2018)
When analyzing President Trump's foreign policy, it is usually agreed that, in some way, its impact on Latin America and the Caribbean has been less direct and relevant or, simply, of a lesser degree than that in Europe and Asia. While this statement may have some truth, the Latin American and Caribbean region is not excluded from the effects of such policy on relevant issues.
Keywords: Estados Unidos--Relaciones exteriores--América Latina; Estados Unidos--Política exterior; https://purl.org/pe-repo/ocde/ford#5.04.05